Problems in medical microbiology - John Holton [et al.] (Blackwell Science, 1995)
This book attempts to provide the student with practice in interpreting laboratory results within the context of a clinical microbiological problem. It covers the entire field of medical microbiology in three sections: bacteriology and mycology, virology, and parasitology